Developing decision support for dialysis treatment of chronic kidney failure. - Raghavan, S.R (IEEE Transactions on information technology in biomedicine)
The complexity, variability, quantitative nature, and data density of treatment for chronic kidney failure make dialysis information systems excellent candidates for computerized decision support. We describe the development of an intelligent system building on existing knowledge and susceptible to reconfiguration on the basis of knowledge acquired during the use of the system. Various decision support techniques were used to design and develop the decision support modules. This paper briefly reviews the literature on clinical decision support, discusses some of the problems faced by practitioners in managing chronic kidney failure (end-stage renal disease) patients, and sets forth the decision support techniques used in developing a dialysis decision support system.